Study of an Online Plan Verification Method and the Sensitivity of Plan Delivery Accuracy to Different Beam Parameter Errors in Proton and Carbon Ion Radiotherapy - Zhao, Jun; Chen, Zhi; Wu, Xianwei; Xing, Ying; Li, Yongqiang (Frontiers in Oncology, 2021)
For scanning beam particle therapy, the plan delivery accuracy is affected by spot size deviation, position deviation and particle number deviation. Until now, all plan verification systems available for particle therapy have been designed for pretreatment verification. The purpose of this study is to introduce a method for online plan delivery accuracy checks and to evaluate the sensitivity of plan delivery accuracy to different beam parameter errors. A program was developed using MATLAB to reconstruct doses from beam parameters recorded in log files and to compare them with the doses calculated by treatment planning system (TPS). Both carbon ion plans and proton plans were evaluated in this study. The dose reconstruction algorithm is verified by comparing the dose from the TPS with the reconstructed dose under the same beam parameters. The sensitivity of plan delivery accuracy to different beam parameter errors was analyzed by comparing the dose reconstructed from the pseudo plans that manually added errors with the original plan dose. For the validation of dose reconstruction algorithm, mean dose difference between the reconstructed dose and the plan dose were 0.70% ± 0.24% and 0.51% ± 0.25% for carbon ion beam and proton beam, respectively. According to our simulation, the delivery accuracy of the carbon ion plan is more sensitive to spot position deviation and particle number deviation, and the delivery accuracy of the proton plan is more sensitive to spot size deviation. To achieve a 90% gamma pass rate with 3 mm/3% criteria, the average spot size deviation, position deviation, particle number deviation should be within 23%, 1.9 mm, and 1.5% and 20%, 2.1 mm, and 1.6% for carbon ion beam and proton beam, respectively. In conclusion, the method that we introduced for online plan delivery verification is feasible and reliable. The sensitivity of plan delivery accuracy to different errors was clarified for our system. The methods used in this study can be easily repeated in other particle therapy centers.